Localising the upper tail: How top income corrections affect measures of regional inequality - Jana Emmenegger; Ralf T. Münnich (Journal of Economics and Statistics, 2023)
Poor coverage of top incomes in surveys, also referred to as the 'missing rich' problem, leads to severe underestimation of income inequality. At the regional level this shortcoming is even more eminent due to small regional sample sizes. Tax records contain more accurate income information at the top and cover all regions equally well. Top-income correction approaches tackle the missing rich problem by imputing top incomes from tax to survey data. While existing methods focus on adjustments at the national level, our paper provides corrections of the regional income distributions in survey data by exploiting the tax data's regional variability. We impute top incomes in the survey data from the German Microcensus based on region-specific Pareto and generalized Pareto distributions estimated from tax records. The combined survey and tax data provide new estimates of regional income inequality in Germany. Our findings indicate that inequality between and within the regions is much larger than previously understood with the magnitude of the adjustment depending on the federal states' level of inequality in the tail.
Keywords: D31; C46; C83; 330; Generalized Pareto distribution; Gini coefficient; spatial income inequality; tax record data